-3+4b=3(b-1)+5

Simple and best practice solution for -3+4b=3(b-1)+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3+4b=3(b-1)+5 equation:



-3+4b=3(b-1)+5
We move all terms to the left:
-3+4b-(3(b-1)+5)=0
We calculate terms in parentheses: -(3(b-1)+5), so:
3(b-1)+5
We multiply parentheses
3b-3+5
We add all the numbers together, and all the variables
3b+2
Back to the equation:
-(3b+2)
We get rid of parentheses
4b-3b-2-3=0
We add all the numbers together, and all the variables
b-5=0
We move all terms containing b to the left, all other terms to the right
b=5

See similar equations:

| 5q-4q+5=14 | | 2b-2b+6b-3=9 | | 1=r/4-3 | | -8v+3v=-8(-3-3v)-4(3v+6) | | -5a+2=7a-46 | | 32=2x+8x | | -7c-3=-83+3c | | X+3x-150=3,150 | | 19s-9s+2=12 | | -7(7-8z)=15-344 | | 1.2/3x=6 | | 51+4a=9a+6 | | 45=-10x-5x | | 12/3x=6 | | 64=-5x+13x | | 4+3+x=11 | | 8-(2n-2)=6-3n | | 3x+5=3.25x | | 11x+6=7x+102 | | 5p+3/4=3p+7/8 | | 7-(2z-6)=9-3z | | 4+3(3)=9x | | 27=7x-4x | | 6q-16q+17q+-4q=-12 | | 3x+1=4x+2/3 | | 5k=17-2 | | 1x/55=180 | | a(a-1)(a+3)=0 | | 5+2x=10x-2x | | 4b=-9+3 | | 2(x+8)-2=35-5x | | 5+4(3x-3)=-2(3x-4)+8x |

Equations solver categories